Split‐graft liver transplantation from an adult donor with an unrecognized UCD to a pediatric and adult recipient. (16th October 2017) - Lee, C. H.; Ellaway, C.; Shun, A.; Thomas, G.; Nair, P.; O'Neill, J.; Shakel, N.; Stormon, M. O.
Abstract: We report the outcomes of an adult and pediatric split liver transplant from an adult male donor who died due to an unrecognized UCD, OTC deficiency. Recognizing inborn errors of metabolism can be challenging, especially in adult centers where such disorders are rarely encountered. Shortage of donors for liver transplantation has led to procedures to maximize donor utilization, such as split and live donor grafts. The cause of death should be ascertained before accepting a cadaveric donor organ.